Pemanfaatan E-Commerce dan Property Management System Dalam Kegiatan Bisnis Perhotelan di Era Revolusi Industri 4.0 - Sutrisno, Eko Yuli; Hidayat, Abdul Choliq; Sutanto, Aftoni (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
This research is motivated by a change in customer’s habits in making hotel reservations online and the use of information systems in hotel operations in the era of the industrial revolution 4.0. Its purpose is to analyze how e-commerce and property management systems in hotel business activities in the 4.0 industrial revolution era. The method used is a qualitative descriptive approach. Data and information collection was at The Atrium Hotel and Resort, Gallery Prawirotaman Hotel, Grand Serela Yogyakarta, Novotel Suite Malioboro, and Cakra Kusuma Hotel Yogyakarta. This study concludes that online travel agents who are part of e-commerce are used in the hotel business because they can cut the reservation process and increase the range of hotel room sales. The property management system is used in the hotel business because it can facilitate the communication and data transfer process by integrating the departments within the hotel. Online travel agents and property management systems are part of a hotel management information system, namely enterprise resource planning (ERP). Both have functions and goals for the efficiency and effectiveness of hotel business activities so that service quality and profit can be achieved maximally in the era of the industrial revolution 4.0